Social Media Data Explication to Support Study on Leadership Style for Sustainable Investing - Natali Hasto Kristijono, Hendrawan Supratikno, Rudy Pramono (International Journal of Control and Automation, 2020)
This article describes the use of social media data to study leadership, specifically  the perception and behaviour of CEOs and corporate leaders towards Sustainable Investing (SI). The world is calling for a more sustainable approach, including investment, towards development following “Our Common Future”, the report by United Nations World Commission on Environment and Development in 1987.  Investment decision making process is closely linked with corporate strategic planning and leadership. Transformational Leadership (TL) theory is used as theoretical base to study the phenomenon of  leadership in SI. Coverage around TL in SI remains scarce, leading to a theory gap. In this inductive, theory-building study, source of data are the leaders of world’s top investment management companies who nowadays are increasingly opening themselves to providing insights on their investment strategies and portfolio to public. Media and social media data collection through the use of public and social media were used due to abundance of readily available materials in the internet, enabling low cost and time efficiency of data collection. Data gathering, storing and preliminary explication approaches are discussed, along with discussion on pros and cons thereof.